RUKUN, SYARAT, DAN MACAM-MACAM AKAD DALAM FIQIH MUAMALAH: STUDI KOMPARATIF EMPAT MAZHAB DAN APLIKASINYA - Bagas Agami Bakti; Mulia Sopiandi Harahap; Qonita Azzahra; Ruhul Zikraini Syafitri; Saifuddin Yuliar (STKIP Subang, 2026)
This study examines the pillars, conditions, and types of contracts in muamalah fiqh through a comparative analysis of the four schools of thought and their application in contemporary economic practice. The background of this study is the complexity of the modern economic system and the discrepancy between classical fiqh concepts and real-world practice, particularly in Islamic financial institutions. This study aims to analyze the similarities and differences in the views of the four schools of thought regarding contracts and to examine their relevance in modern economic transactions. The method used is a qualitative approach involving library research, through the review of classical fiqh literature, scientific journals, and other relevant sources. Data analysis was conducted using a descriptive-analytical approach by synthesizing various opinions of scholars. The results of the study indicate that there are differences in the determination of the essential elements (rukun) and conditions (syarat) of contracts, particularly in the Hanafi school, which emphasizes the contractual formula (sighat) as the primary essential element, while the other schools consider all elements to be essential. Nevertheless, all schools share the same objective: to uphold justice and legal certainty. Furthermore, various types of contracts, whether tabarru’ or tijarah, remain relevant and adaptable in the context of the modern economy, such as digital transactions and Islamic banking. This study affirms that differences of opinion among the schools of thought constitute an intellectual asset that provides flexibility in the development of an Islamic economy that remains grounded in Sharia principles.